A legitimação do Estado democrático de direito para além da decretação abstrata de constitucionalidade: o valor prospectivo da interpretação conforme à Constituição como desdobramento concreto entre a lei e o direito - Reis, Maurício Martins (Universidade do Vale do Rio do Sinos, 2009)
This PhD thesis highlights as the very problematic/debatable binding element the concept, the reach and the peculiarities undeniably inherent in the constitutionally appropriate interpretation. The application of the law consists of a hermeneutic and normative procedure of fulfilling specificity which aims at solving the opposing conflicts in court through a materially legitimate decision-making statement. The decisions analyzed by the justice system must, in their substantiated content, be in conformity with the constitutional provisions, either applying the normative acts in agreement with the Constitution, either addressing adequately and effectively the material law that has been unfairly sacrificed or threatened. This way, the constitutional judgement acquires judicial autonomy of concrete nature or jurisdictionally decisory in face of what has been denominated constitutional control of the laws. The unconstitutionality of the laws, thus, can not be put on the same level of the unconstitutionality as t
Keywords: aplicação jurisdicional; controle de constitucionalidade; hermenêutica filosófica; interpretação conforme à Constituição; interpretação jurídica; jurisdição constitucional; tribunais constitucionais; constituição; constitutional control; constitutional courts; constitutional jurisdiction; constitutionality; judicial interpretation; jurisdictional application; philosophical hermeneutics; constitution; Ciências Sociais Aplicadas